1
$\begingroup$

Suppose you have this two Lipschitz continuous functions:

$f_1$ ,with constant $L_1$ and $f_2$ with constant $L_2$.

I have to prove that $f_2 - f_1$ is Lipschitz continuous with constant $L_1+L_2$.

I did like this:

$|(f_2-f_1)(y)-(f_2-f_1)(x)|=|f_2(y)-f_2(x)-f_1(y)+f_1(x)|=$

$=|(f_2(y)-f_2(x))+(-f_1(y)+f_1(x))|$

By the triangle inequality:

$\leq|f_2(y)-f_2(x)|+|-f_1(y)+f_1(x)|$

$\leq L_2|y-x|+|-y+x|$

But I´m having problems in this last line,above...I should have $|y-x|$ in both,isn´t it?What´s wrong?how to proceed?Thanks?

$\endgroup$
  • 1
    $\begingroup$ You are missing at $L_1$ on the last line of your formula. Also, $|z| = |-z|$, so $|-y+x| = |x-y| = |y-x|$. $\endgroup$ – copper.hat Jul 12 '12 at 19:42
1
$\begingroup$

One of the properties of a norm tells you that $|\lambda u|=|\lambda||u|$ for every scalar $\lambda$ and every vector $u$. Therefore $|-f_1(y)+f_1(x)|=|f_1(y)-f_1(x)|\le L_1|y-x|$ .

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.